2002
DOI: 10.1021/jp0138779
|View full text |Cite
|
Sign up to set email alerts
|

New Substrates for the Oscillating Briggs−Rauscher Reaction

Abstract: Several new organic substrates have been found to promote oscillations in batch conditions in the Briggs−Rauscher oscillating system. The new substrates, crotonic acid, acrylic acid, anisole, and p-nitrophenol, react with iodine (I) by either addition or substitution reactions. Rate constants for reactions of these four compounds with HOI have been determined. Previously known substrates have active methylene hydrogens and react with I2 via an enol mechanism. Some type of active reduction of HIO2 to HOI (other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
70
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 21 publications
1
70
0
1
Order By: Relevance
“…oscillations has been recognized in previous work [6] [7]. We have ascribed inhibitory effects to the antioxidants× scavenging action against HOO .…”
mentioning
confidence: 64%
“…oscillations has been recognized in previous work [6] [7]. We have ascribed inhibitory effects to the antioxidants× scavenging action against HOO .…”
mentioning
confidence: 64%
“…In 2002, Furrow et al [29] reported a 13-step new mechanism (named FCA model) for the Briggs -Rauscher reaction that takes into account the important role played by HOO . radicals in its oscillatory behavior.…”
mentioning
confidence: 99%
“…This mixture was allowed to stir overnight until it was clear. In both Steps D1, M, D2, D3, I5R, O2, and I3 were taken from the FCA (Furrow, Cervellati, Amadori) mechanism that was found effective in simulating the BR oscillator with malonic acid and its C(2) substituted derivatives, as well as with other substrates that iodinate in a different way [16]. These steps represent the oxyiodine intermediate reactions and the formation and consumption of radicals.…”
Section: Results -Behavior Of the Completely Unperturbed And Perturbmentioning
confidence: 99%